2020
DOI: 10.1371/journal.pone.0233440
|View full text |Cite
|
Sign up to set email alerts
|

Sexual norms and the intention to use healthcare services related to female genital cutting: A qualitative study among Somali and Sudanese women in Norway

Abstract: Background Female Genital Cutting (FGC) is a traditionally meaningful practice in Africa, the Middle East, and Asia. It is associated with a high risk of long-term physical and psychosexual health problems. Girls and women with FGC-related health problems need specialized healthcare services such as psychosexual counseling, deinfibulation, and clitoral reconstruction. Moreover, the need for psychosexual counseling increases in countries of immigration where FGC is not accepted and possibly stigmatized. In thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Consequently, FGC-related problems may be context specific. Studies have demonstrated that psychosexual complaints are higher in low-prevalence countries than in high-prevalence ones [16,17]. One explanation might be that FGC is normalized in high-prevalence countries so that its effects are taken for granted whilst this might not be the case in low-prevalence countries.…”
Section: Fgc and The Effect On Health Sexuality And Bodily Identitymentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, FGC-related problems may be context specific. Studies have demonstrated that psychosexual complaints are higher in low-prevalence countries than in high-prevalence ones [16,17]. One explanation might be that FGC is normalized in high-prevalence countries so that its effects are taken for granted whilst this might not be the case in low-prevalence countries.…”
Section: Fgc and The Effect On Health Sexuality And Bodily Identitymentioning
confidence: 99%
“…Another may be that women are enabled to speak out about these effects in one context but not in another. Yet another explanation might be that exposure to educational material about the negative effects of FGC on sexual function makes women experience problems they would otherwise not recognize if not exposed to such messages [16]. On the other hand, it may be that the educational material enables women already experiencing sexual dysfunction to make sense of and report sexual dysfunction.…”
Section: Fgc and The Effect On Health Sexuality And Bodily Identitymentioning
confidence: 99%
See 3 more Smart Citations